Jejunal Varices Bleeding in a Patient with Extensive Portomesenteric Thrombosis Secondary to Factor V Leiden Mutation: A Management Dilemma - Ahmad Ayash; Kamran Mushtaq; Mohamed Emad Abdul Qader; Khalid Mohsin Al-Ejji; Saad Rashid Al Kaabi; Shadi J. S. Khelfa (Case Reports in Gastrointestinal Medicine)
Ectopic varices are portosystemic collaterals that occur away from the gastroesophageal junction and account for 1-5% of all variceal bleeding. Its occurrence in the jejunum is rare. Most common cause of ectopic jejunal varices is portal hypertension especially in those patients who have undergone prior abdominal surgery. Portomesenteric thrombosis is a rare cause of ectopic jejunal varices. Ectopic varices are rare cause of obscure GI bleeding and hence should be always suspected in patients with history of portal hypertension who present with GI bleeding and have negative upper and lower GI endoscopies. Management of patients with ectopic varices is often very challenging and requires multidisciplinary approach. Therapeutic options include endoscopic therapy, interventional radiologic procedures, surgically creating shunting, or surgical resection. We present the case of a 52-year-old patient who was on anticoagulation for extensive portomesenteric thrombosis secondary to factor V Leiden heterozygous mutation and presented with melena and symptomatic anemia. Investigations showed bleeding jejunal varices as the cause of anemia. We discuss the therapeutic options and dilemma in the management of such cases.